THE EFFECT OF MOTIVATION, TRANSFORMATIONAL LEADERSHIP, AND SOCIAL SUPPORT ON PERSONNEL PERFORMANCE THROUGH WORKLOAD PROPORTIONALISM IN THE EAST KALIMANTAN REGIONAL POLICE INVESTIGATION - Teddy Chandra; Irsan Tricahyadinata; Wirasmi Wardhani (RADJA PUBLIKA, 2026)
This study examines the influence of work motivation, transformational leadership, and social support on personnel performance through workload proportionalism at the Narcotics Criminal Investigation Directorate (Ditresnarkoba) of East Kalimantan Regional Police (Polda Kaltim). The research employs a quantitative explanatory approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.3.9, involving 80 personnel as respondents selected through purposive sampling. Results indicate that work motivation, transformational leadership, and social support each positively and significantly influence workload proportionalism. Transformational leadership, social support, and workload proportionalism also significantly and positively affect personnel performance directly. However, work motivation does not directly influence performance, suggesting full mediation through workload proportionalism. Workload proportionalism partially mediates the effects of transformational leadership and social support on performance. These findings confirm that workload proportionalism is a critical mediating construct integrating Self-Determination Theory, Transformational Leadership Theory, and Social Support Theory in high-pressure organizational contexts.